Physicochemical and structural properties of starch from young bamboo culm of Bambusa tuldoides - Felisberto, Mária Herminia Ferrari; Beraldo, Antonio Ludovico; Costa, Mariana Souza [UNESP]; Boas, Flávia Villas [UNESP]; Franco, Célia Maria Landi [UNESP]; Clerici, Maria Teresa Pedrosa Silva (Elsevier, 2019)
Starch is used in a wide variety of food and non-food industrial applications. However, in some cases, it is necessary to apply physical and/or chemical treatments to alter some properties, besides being an expensive process, it is environmentally unfriendly. So, the objective of this study was to characterize the morphology, structure, physicochemical and thermal properties of starch extracted from three different parts of the young culm (bottom-SB, middle-SM and top-ST) of B. tuldoides. The obtained data were evaluated by ANOVA and Scott-Knot test (p < 0.05). The starches presented pale yellow coloration and high luminosity (on average a* = 0.65, b* = 11.26 and L = 89.39), besides polyhedral shape and small size (on average 4.64 μm) observed by optical (OM) and scanning electron (SEM) microscopies. The starches showed apparent amylose content similar to starches from cereals and isolated from bamboo seeds. The molecular size distribution of amylose chains corroborates with SM (33.35%) and ST (24.48%) amylose content, since they presented the highest values. The highest proportion of chains of amylopectin were observed for DP 13–24, without significant difference between the samples, which sustain with A-type polymorph presented for all the samples. Transition temperature above 81 °C was observed and agree with the higher proportions of amylopectin short chains. The obtained starches presented characteristics of native starches and were similar to the starches traditionally used. Thus, starch from the young culm of bamboo would be an alternative source to traditional starches, such as rice, wheat or corn, sustaining with its potential for industrial applications.
Keywords: Carbohydrate; Grass; Industrial application; Morphology; Properties; Sustainability environment